1987
DOI: 10.1002/hep.1840070713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of persistent woodchuck hepatitis virus and hepatitis B virus infection and hepatocellular carcinoma

Abstract: It seems evident that the development of fully malignant HCC is a multistage process with many variables. One possible mechanism by which many of these variables may interact is as follows. During chronic active hepatitis, viral DNA integration occurs randomly and at a low frequency in hepatocytes. Integration may be stimulated by the increased rate of hepatocyte cell division resulting from liver necrosis and regeneration during chronic disease. The presence of viral integrations in the cellular genome provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study, as well as previous reports (9. 27: 35-38). 40), demonstrates that the woodchuck is also suitable as an experimental virus infection model for the determination of risk factors for HCC development associated with hepadnavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This study, as well as previous reports (9. 27: 35-38). 40), demonstrates that the woodchuck is also suitable as an experimental virus infection model for the determination of risk factors for HCC development associated with hepadnavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The only available treatment for chronic hepatitis B is interferon-a (IFN-a), which has less than 50% efficacy even in highly selected patients. It also has been shown that the HBV infection could relate to later hepatocellular carcinoma (Tiollaia et al, 1985;Rogler et al, 1987;Offensperger et al, 1994). HBV belongs to the hepadnavirus family, which also includes woodchuck hepatitis virus (WHV), ground squirrel hepatitis virus (GSHV), and duck hepatitis B virus (DHBV) (Mason et al, 1980;Cullen et al, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…The plus strand usually is not completed before the coating of the nucleocapsids. In chronic infection hosts, the integrated DNA has been detected (Rogler et al, 1987), and liver histologie changes have been reported (Freiman et al, 1988). Because the viral infection is considered to be an acquired genetic disease (Anderson, 1992;Morgan and Anderson, 1993), with the overexpression or expression of the acquired genes, it could also be used in the therapeutic treatment by gene blocking at either the transcription or translation level.…”
Section: Introductionmentioning
confidence: 97%
“…Multiple animal models of HBV infection have been utilized over the past four decades including the Peking duck 4 , 5 , woodchuck 6 8 , mouse 9 , 10 , and chimpanzee 11 13 . These models have contributed significantly to our understanding of virus-host interactions, but each have drawbacks that limit their utility for drug development.…”
Section: Introductionmentioning
confidence: 99%